2015
DOI: 10.1002/jcc.23944
|View full text |Cite
|
Sign up to set email alerts
|

A comparative computationally study about the defined m(II) pincer hydrogenation catalysts (m = fe, ru, os)

Abstract: The mechanism of acetonitrile and methyl benzoate catalytic hydrogenation using pincer catalysts M(H)2 (CO)[NH(C2 H4 PiPr2 )2 ] (1M) and M(H)(CO)[N(C2 H4 PiPr2 )2 ] (2M) (M = Fe, Ru, Os) has been computed at various levels of density functional theory. The computed equilibrium between 1Fe and 2Fe agrees perfectly with the experimental observations. On the basis of the activation barriers and reaction energies, the best catalysts for acetonitrile hydrogenation are 1Fe/2Fe and 1Ru/2Ru, and the best catalysts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
4
26
1
Order By: Relevance
“…Since both water and methanol have been reported to lower the barriers of catalyst regeneration, we explored such effect of PhCH 2 OH as proton shuttle for the interconversion between 1M and 2M in gas phase and in PhCH 2 OH. A two‐step mechanism corresponding to proton transfer from PhCH 2 OH to the nitrogen atom of the ligand as well as H–H cleavage was located.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both water and methanol have been reported to lower the barriers of catalyst regeneration, we explored such effect of PhCH 2 OH as proton shuttle for the interconversion between 1M and 2M in gas phase and in PhCH 2 OH. A two‐step mechanism corresponding to proton transfer from PhCH 2 OH to the nitrogen atom of the ligand as well as H–H cleavage was located.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, B3PW91 has been used successfully in other metal based pincer complexes. [29a], All structures were optimized at the B3PW91 level with the TZVP basis set (LANL2DZ for Mn and Re). All optimized structures were characterized either as energy minimums without imaginary frequencies or transition states with only one imaginary mode by frequency calculations; and the transition state connects the initial and the final states.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the final step, intermediate B forms amine C, while 9 is regenerated by the addition of H 2 to 10. In our recent computational work, [16] we found that ruthenium complex 9Ј (isopropyl instead of phenyl) should also catalyze the nitrile hydrogenation by the same outersphere reaction mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…Presumably, complex C1 b is activated through metal‐ligand‐cooperation, which is typical for pincer complexes bearing an amine functionality and/or a benzylic position which can be deprotonated . This could lead to the ruthenium diyhdride species C1 b‐H (Scheme ).…”
Section: Resultsmentioning
confidence: 99%